Complementary strategies for teaching Chemistry (Research, Society and Development, 2021)
This work consists of an experience report of an extension project that was developed with the objective of improving the discipline of Chemistry in the second year classes (High School and EJA) of the State Schools of Bambuí, Minas Gerais. To achieve this goal, the team sought to use different didactic-pedagogical strategies. While in one of the schools the game "Hot or Cold?" in the approach to the thermochemistry content, in another school we sought to employ the experimental activity “CO2 solubility in the refrigerant- pressure effect” and contextualization texts related to the contents of solutions and solubility. For these latter contents, activities were proposed, consisting of eight objective questions. From the results obtained, it was possible to verify that the didactic game contributed to the diagnosis of problems related to the content of the theme involved, as well as to motivate students during the performance of the proposed activity, creating conditions for new ways of thinking. Experimentation was considered as a didactic-pedagogical resource that favors the consolidation of teaching, since the concepts associated with it were more successful in the quantitative analysis of the proposed activities. Finally, it was found that the insertion of complementary texts linked to daily life contributed to the formation of critical citizens, capable of acting in real situations. Through the analysis of the results obtained, the participants of the extension team believe that the project motivated the teachers in their practice and the students in their preconceptions.